2017
DOI: 10.14740/jocmr2925w
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Diastolic Function Assessment of a Heterogeneous Cohort of Pulmonary Arterial Hypertension Patients

Abstract: BackgroundPulmonary arterial hypertension (PAH) is known to trigger right ventricular (RV) remodeling that might compromise left ventricular (LV) filling due to inter-ventricular interdependence. In this study, we aimed to examine standard echocardiographic measurements of LV diastolic function in PAH patients.MethodsIn this retrospective study, we identified clinical as well as complete echocardiographic data from 128 chronic PAH patients to fully assess LV diastolic dysfunction (LVDD) using standard recommen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
3
0
2
Order By: Relevance
“…Em 2016, um estudo analisou as tendências relacionadas à HAP em adultos, nos Estados Unidos, e demonstrou que a hipertensão arterial (5,1-17,1%), a diabetes (4,6-7,8%) e a doença coronariana (15,6-22,3%) são comorbidades frequentemente associadas. A insuficiência cardíaca congestiva (40,7-56,1%) e a doença renal aguda (5,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20),1%) e crônica (1,1-16,4%) também aparecem como fatores importantes 22 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Em 2016, um estudo analisou as tendências relacionadas à HAP em adultos, nos Estados Unidos, e demonstrou que a hipertensão arterial (5,1-17,1%), a diabetes (4,6-7,8%) e a doença coronariana (15,6-22,3%) são comorbidades frequentemente associadas. A insuficiência cardíaca congestiva (40,7-56,1%) e a doença renal aguda (5,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20),1%) e crônica (1,1-16,4%) também aparecem como fatores importantes 22 .…”
Section: Discussionunclassified
“…Uma PSAP > 35 mmHg, medida por cateterismo cardíaco direito, corresponde à pressão média da artéria pulmonar > 25 mmHg. Portanto, valores de PSAP ≥ 35 mmHg, medidos pelo ecocardiograma, sugerem HAP, assim como aumento de câmaras direitas, insuficiência tricúspide, movimento paradoxal do septo interventricular e diminuição da complacência do ventrículo esquerdo 3,5 . O ecocardiograma deve ser sempre realizado em caso de suspeita de HAP e pode ser usado para inferir o diagnóstico em doentes nos quais diferentes medidas ecocardiográficas estejam consistentes com o diagnóstico 6 .…”
Section: Introductionunclassified
“…Probably, chronic myocardial ischemia caused by arterial constriction was responsible for the cardiac function change, being related with the coronary artery lesion severity. Studies found that for patients with angina pectoris and coronary heart disease, myocardial ischemia degree and cardiac function condition predominantly determined the prognosis 14,15. Relevant vascular revascularization may be conducive to improving the prognosis 16…”
Section: Discussionmentioning
confidence: 99%
“…LV diastolic function was classified as normal (LVDD 0), impaired relaxation (LVDD 1), and pseudonormal pattern (LVDD 2). All echocardiographic parameters including LV volumes, LVEF, left atrial volume index, LV mass, MAPSE, and all Doppler variables used to determine LV diastolic function were measured as previously reported by our group [10, 11].…”
Section: Methodsmentioning
confidence: 99%